The Influence of Father Involvement on the Relationship Between Maternal Postpartum Depression and Infant Self-Regulation - Manzo, Victoria; Chen, Sarah (My University, 2025)
Self-regulation is defined as the ability to control immediate responses due to immediate environmental stimuli (Davis et al., 2017). Both infant temperament and self-regulation later predict patterns in emotional adjustment, school performance, socialization, and internalizing/externalizing behaviors (Davis et al., 2017; Backer & Nærde, 2017). Maternal psychopathology is a component of the family system that has been investigated on its relations to self-regulation development. Multiple studies have supported the idea that maternal depression is negatively associated with the child’s self-regulation abilities (Granat et al., 2017, Feldman et al., 2009). While many studies have focused on this topic of maternal influence on the development of self-regulation, very little literature is available on father involvement, and it’s influence on the relationship.
Keywords: UMBC PSYC 499H - 29